2014
DOI: 10.29252/ijn.27.88.77
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture from Mazandaran Clinical Nurses’ Perspective

Abstract: Background & Aim: Nurses are one the important groups in patients" recovery and safety and have an important role in the reduction of their mortality. The aim of the study was to identify nurses" perceptions of patient safety culture in Mazandaran"s hospitals. Material & Methods: It was a descriptive correlational study which has been done in a two month period in the hospitals of Tonekabon, Chaloos, and Ramsar. The sample was recruited by census (n= 456). Data was collected by Persian version of HSOPS, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, lecturebased learning become inevitable for everyone at some point and could be useful for providing basic information (16). Some studies have demonstrated a significant relationship between variables such as age, work experience (17), and education level (18) with patient safety. However, we did not observe any relationship between patient safety and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, lecturebased learning become inevitable for everyone at some point and could be useful for providing basic information (16). Some studies have demonstrated a significant relationship between variables such as age, work experience (17), and education level (18) with patient safety. However, we did not observe any relationship between patient safety and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Over all mean safety culture was 3.28 ± 0.27, which indicates moderate level of patient safety culture among nurses. Results of Sharifi,17 Rezapour et al, 18 and Almasi et al 19 also showed that the status of patient safety culture was moderate among hospital nurses. This is in line with the results of present study.…”
Section: Discussionmentioning
confidence: 93%
“…(2015), level of patient safety culture was reported to be low-to-moderate. [ 15 ] In some other studies,[ 9 16 17 ] safety culture points were reported to be low in some dimensions that require emergency intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Nurses are considered to be the most influential members of the health team in providing safe care and have an important role in care and patient safety. [ 9 ] Twenty-four hour nurse–patient relationship enables the nurses to provide the information necessary to identify the problems of the health system as a part of patient safety solutions. In a hospital, with a desirable safety culture, nurses should be able to express their opinions freely, and report cases where an adverse event is happening due to system problems or human factors.…”
Section: Introductionmentioning
confidence: 99%